Development of DPIB Basics E-Module at SMK Dhuafa Padang - Masrizal; M. Giatman; Fahmi Rizal; Yeka Hendriyani; Meiyaldi Eka Putra (Postgraduate, University of Mataram, 2024)
In this research, the 4D model development stages (Define, Design, Develop, and Disseminate) were used which include needs analysis, design, development, and dissemination. The validation results of media experts and material experts show that this E-Module is very suitable with a validity percentage of 75.78% by experimental group experts and 64.67% by control group experts. These results indicate that the E-Module developed through the 4D model is suitable for use in the learning process. The development of E-Modules in vocational schools can be an effective solution to overcome the challenges of students' understanding and skills in DPIB subjects. By using a 4D model in its development, high validation results from media and material experts show that this E-Module has very good quality. It is hoped that the use of this E-Module can improve students' understanding and skills in basic areas that are important for preparation for the world of work. Furthermore, this research also provides recommendations for E-Modules in the broader context of learning, teacher training and other material development.